ARI updates 2021 / Accounting Research Institute - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2021)
In tandem with the government’s aspiration to make Malaysia a global Islamic Finance Hub, ARI’s research in Islamic Financial Criminology is not justtimely, but extremely crucial to support a sustainable Islamic Finance Industry.